Efisiensi dan Efektivitas Penggunaan Mesin Curito sebagai Alat Penghancur Bahan-bahan yang Digunakan untuk Operasional di Perkebunan Kelapa Sawit - Rio Dwi Fernando; Toto Suryanto; Aang Kuvaini; Yudi Dermawan (Politeknik Kelapa Sawit Citra Widya Edukasi, 2016)
The purpose of this study was to get crushing tool tufts fertilizer and provision of material the road for operation fertilizing and the road that can add work performance, get efficiency and effectiveness instrument curito of the operational fertilizing and provision of material the road in the palm oil plantation. Method to research this is the method approach design in general namely approach the functional architecture. Shredder fertilizer work in a radial manner with mounted a screw to enumerate smoking fertilizer which has been hardened. Crushing is done in tube machines and the final step in process is being away who next in apply them to garden palm oil. Effective capacity rate are 191.3 kg/hour for tufts fertilizer urea, 58 kg/hour for brick and 120 kg/hour for adobe.